Lenalidomide Causes Selective Degradation of IKZF1 and IKZF3 in Multiple Myeloma Cells - Krönke, Jan (2013)
Lenalidomide is a drug with clinical efficacy in multiple myeloma and other B cell neoplasms, but its mechanism of action is unknown. Using quantitative proteomics, we found that lenalidomide causes selective ubiquitination and degradation of two lymphoid transcription factors, IKZF1 and IKZF3, by the CRBN-CRL4 ubiquitin ligase. IKZF1 and IKZF3 are essential transcription factors in multiple myeloma. A single amino acid substitution of IKZF3 conferred resistance to lenalidomide-induced degradation and rescued lenalidomide-induced inhibition of cell growth. Similarly, we found that lenalidomide-induced IL2 production in T cells is due to depletion of IKZF1 and IKZF3. These findings reveal a novel mechanism of action for a therapeutic agent, alteration of the activity of an E3 ubiquitin ligase leading to selective degradation of specific targets.